A Sparse Recovery Approach for Pattern Correction of Active Arrays in Presence of Element Failures - Migliore, Marco Donald; Pinchera, Daniele; Lucido, Mario; Schettino, Fulvio; Panariello, Gaetano (IEEE antennas and wireless propagation letters, 2015)
The aim of this letter is to propose a novel approach based on sparse recovery technique for real-time correction of the pattern of active arrays in presence of failures of radiating elements. The failures are identified without interfering with the normal array operation, using a small number of probes placed around the array. After identifying the faulty elements, the aperture is reconfigured in order to reduce the pattern degradation as much as possible.